The quality of afterlife: surviving extracorporeal life support after therapy‐refractory circulatory failure—a comprehensive follow‐up analysis - Moritz Benjamin Immohr; Sophie Margaretha Eschlböck; Philipp Rellecke; Hannan Dalyanoglu; Igor Tudorache; Udo Boeken; Payam Akhyari; Alexander Albert; Artur Lichtenberg; Hug Aubin (ESC Heart Failure, 2021)
Abstract Aims Extracorporeal life support (ECLS) represents a popular treatment option for therapy‐refractory circulatory failure and substantially increases survival. However, comprehensive follow‐up (FU) data beyond short‐term survival are mostly lacking. Here, we analyse functional recovery and quality of life of longer‐term survivors. Methods and results Between 2011 and 2016, a total of n = 246 consecutive patients were treated with ECLS for therapy‐refractory circulatory failure in our centre. Out of those, 99 patients (40.2%) survived the first 30 days and were retrospectively analysed. Fifty‐eight patients (23.6%) were still alive after a mean FU of 32.4 ± 16.8 months. All surviving patients were invited to a prospective, comprehensive clinical FU assessment, which was completed by 39 patients (67.2% of survivors). Despite high incidence of early functional impairments, FU assessment revealed a high degree of organ and functional recovery with more than 70% of patients presenting with New York Heart Association class ≤ II, 100% free of haemodialysis, 100% free of moderate or severe neurological disability, 71.8% free of moderate or severe depression, and 84.4% of patients reporting to be caring for themselves without need for assistance. Conclusions Patients surviving the first 30 days of ECLS therapy for circulatory failure without severe adverse events have a quite favourable outcome in terms of subsequent survival as well as functional recovery, showing the potential of ECLS therapy for patients to recover. Patients can recover even after long periods of mechanically support and regain physical and mental health to participate in their former daily life and work.